Extending the effective bandwidth concept to networks with priority classes. - Berger, A.W.
ATM switches are now being designed to allow connections to be partitioned into priority classes, with packets being emitted for higher priority classes before packets are emitted for lower priority classes. Accordingly, allocation of network resources based on different priority levels is becoming a realistic possibility. Thus, we need new methods for connection admission control and capacity planning that take account of the priority structure. We show that the notion of effective bandwidths can be used for these purposes when appropriately extended. The key is to have admissibility of a set of connections determined by a linear constraint for each priority level, involving a performance criterion for each priority level. For this purpose, connections are assigned more than one effective bandwidth, one for its own priority level and one for each lower priority level. Candidate effective bandwidths for each priority level can be determined by using previous methods associated with the first-in first-out discipline. The proposed effective bandwidth structure makes it possible to apply product-form stochastic loss network models to perform dimensioning
Keywords: ATM switches; Connection admission control; Effective bandwidth; First-in first-out discipline; Linear constraint; Network capacity planning; Network dimensioning; Network resource allocation; Performance criterion; Priority classes; Priority level; Product-form stochastic loss; Network models